Exploring semantic and phonological picture-word priming in adults who stutter using event-related potentials - Maxfield, Nathan D. (2011)
OBJECTIVE: Our aim was to investigate how semantic and phonological information is processed in adults who stutter (AWS) preparing to name pictures, following-up a report that event-related potentials (ERPs) in AWS evidenced atypical semantic picture-word priming (Maxfield et al., 2010). METHODS: Fourteen AWS and 14 typically-fluent adults (TFA) participated. Pictures, named at a delay, were followed by probe words. Design elements not used in Maxfield et al. (2010) let us evaluate both phonological and semantic picture-word priming. RESULTS: TFA evidenced typical priming effects in probe-elicited ERPs. AWS evidenced diminished Semantic priming, and reverse Phonological N400 priming. CONCLUSIONS: Results point to atypical processing of semantic and phonological information in AWS. Discussion considers whether AWS ERP effects reflect unstable activation of target label semantic and phonological representations, strategic inhibition of target label phonological neighbors, and/or phonological label-probe competition. SIGNIFICANCE: Results raise questions about how mechanisms that regulate activation spreading operate in AWS.